Growth of White Leghorn Chicken Immune Organs after Long-Term Divergent Selection for High or Low Antibody Response to Sheep Red Blood Cells - Christa F. Honaker; Robert L. Taylor; Frank W. Edens; Paul B. Siegel (Animals, 2024)
Long-term divergent selection from a common founder population for a single trait—antibody response to sheep erythrocytes 5 days post-injection—has resulted in two distinct lines of White Leghorn chickens with a well-documented difference in antibody titers: high (HAS)- and low (LAS)-antibody selected lines. Subpopulations—high (HAR)- and low (LAR)-antibody relaxed—were developed from generation 24 of the selected lines to relax selection. The objective of the current experiment was to determine if this long-term selection and relaxation of selection impacted the growth of two organs important to chicken immunity: the spleen and the bursa of Fabricius. Spleens and bursae were obtained from ten chickens per line at nine timepoints (E18, D0, D6, D13, D20, D35, D49, D63, and D91) throughout their rapid growth phase and presented as a percent of body weight. Significance was set at p ≤ 0.05. For the spleen, all lines consistently increased in size relative to body weight to D49, followed by a consistent decline. All lines had a similar growth pattern, but HAS spleens grew faster than LAS spleens. For the bursa, LAS was smaller than the other three lines as an embryo and also smaller than HAS through D63. In the selected lines, bursa weight peaked at D35, whereas the relaxed lines peaked at D49. By D91, there was no difference between lines. Artificial and natural selection, represented by the long-term selected and relaxed antibody lines, resulted in differences in the growth patterns and relative weights of the spleen and bursa of Fabricius.